2014
DOI: 10.1038/nm.3618
|View full text |Cite|
|
Sign up to set email alerts
|

Micropillar arrays as a high-throughput screening platform for therapeutics in multiple sclerosis

Abstract: Functional screening for compounds that promote remyelination represents a major hurdle in the development of rational therapeutics for multiple sclerosis. Screening for remyelination is problematic, as myelination requires the presence of axons. Standard methods do not resolve cell-autonomous effects and are not suited for high-throughput formats. Here we describe a binary indicant for myelination using micropillar arrays (BIMA). Engineered with conical dimensions, micropillars permit resolution of the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
503
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 498 publications
(522 citation statements)
references
References 27 publications
12
503
1
6
Order By: Relevance
“…Preclinical work validated the efficacy of clemastine fumarate in vitro and in animal models. 17,19 Additional work confirmed the efficacy of clemastine fumarate in multiple animal models [17][18][19][20][21][22] and showed that this benefit was mediated specifically via remyelination induced from oligo dendrocyte differentiation and not via effects on the immune system. 19 We furthermore showed the capacity of clemastine fumarate to induce oligodendrocyte progenitor cell (OPC) differentiation and myelination with human OPCs (appendix).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Preclinical work validated the efficacy of clemastine fumarate in vitro and in animal models. 17,19 Additional work confirmed the efficacy of clemastine fumarate in multiple animal models [17][18][19][20][21][22] and showed that this benefit was mediated specifically via remyelination induced from oligo dendrocyte differentiation and not via effects on the immune system. 19 We furthermore showed the capacity of clemastine fumarate to induce oligodendrocyte progenitor cell (OPC) differentiation and myelination with human OPCs (appendix).…”
Section: Introductionmentioning
confidence: 79%
“…Preclinical data unequivocally showed that clemastine fumarate promotes oligodendrocyte precursor differentiation 17,18 and remyelination [19][20][21][22] without modulating the immune system. 19 The robustness of the findings were documented by the latency improvement observed in both groups of the cohort while on active treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the ventral white matter makes up a much larger target area to inject; several hundred microns laterally in the dorsal region would place the capillary outside the column, while the same deviation ventrally would still produce a prominent demyelinating lesion. Some protocols inject lysolecithin into both the dorsal and ventral columns of the same animal 19 . This can increase both the likelihood of proper capillary placement and the number of quantifiable lesions in fewer animals.…”
Section: Discussionmentioning
confidence: 99%
“…Purification of rodent or murine OPCs either through differential antibody binding (panning) or FACS sorting allows for assessment of the direct response of the cell population to therapeutic exposure. Such approaches have been used recently to identify signaling mechanisms that promote the appearance of mature oligodendrocytes [75][76][77][78]. One concept that has gained significant support in recent years is the notion that the rate-limiting step in remyelination is the differentiation and maturation of oligodendrocytes to myelinating cells.…”
Section: In Vitro Discovery Platforms For Therapeutic Developmentmentioning
confidence: 99%